Respon Pertumbuhan Stek Cassia Tora pada Perlakuan Konsentrasi Zat Pengatur Tumbuh Auksin - Danie Indra Yama (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
The fire caterpillar predator and fire caterpillar parasitoid require food from the wrong plant the only one is the nectar of Cassia tora. Therefore it is necessary to accelerate the growth of Cassia tora so that the nectar of Cassia tora can also be quickly available. Vegetative propagation of cuttings with rootone-f treatment is one way to accelerate the propagation and supply of nectar. The purpose of this research is to know the influence of rootone-f concentration on growth and development of Cassia tora, to know the parameters that affect dry weight of plants, to obtain optimal rotoone-f concentration for growth and development of Cassia tora cuttings. The research was conducted on March to May 2017 in PT Satu Sembilan Delapan, East Kalimantan, using Complete Randomized Block Design (CRBD) method, with rootone-f concentration of R1: 1 g/200 ml, R2: 2 g/200 ml, R3: 3 gr/200 ml. The observed data were analyzed with variance at 5% real level, to know the real difference between treatments tested further with LSD (Least Significance Different). The rootone-f aplication had significant effect on plant height 3-6 week after planting and stem diameter at 5, 7 and 8 week after planting. The plant height parameters influenced or positively correlated with dry weight of the plant. The concentration of rootone-f 2 g/200 ml is a good concentration for plant growth of Cassia tora especially to increase the height of the plant.